2021
DOI: 10.1039/d1ra02876f
|View full text |Cite
|
Sign up to set email alerts
|

Effective inhibition and eradication of pathogenic biofilms by titanium dioxide nanoparticles synthesized using Carum copticum extract

Abstract: Titanium dioxide nanoparticles inhibits and eradicates the biofilms of pathogenic bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…It was shown that the amount of biofilm mass decreased with an increasing concentration of nanoforms. Fatima et al [ 50 ] and Altaf et al [ 51 ] obtained similar results. Fatima et al [ 50 ] showed that exposure of oral bacterial strains ( Georgenia sp., Staphylococcus saprophyticus , and Rothia mucilaginosa ) to titanium dioxide nanoparticles (TiO 2 -NPs) significantly reduced biofilm formation in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It was shown that the amount of biofilm mass decreased with an increasing concentration of nanoforms. Fatima et al [ 50 ] and Altaf et al [ 51 ] obtained similar results. Fatima et al [ 50 ] showed that exposure of oral bacterial strains ( Georgenia sp., Staphylococcus saprophyticus , and Rothia mucilaginosa ) to titanium dioxide nanoparticles (TiO 2 -NPs) significantly reduced biofilm formation in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…Fatima et al [ 50 ] showed that exposure of oral bacterial strains ( Georgenia sp., Staphylococcus saprophyticus , and Rothia mucilaginosa ) to titanium dioxide nanoparticles (TiO 2 -NPs) significantly reduced biofilm formation in a concentration-dependent manner. The presence of TiO 2 -NPs at concentrations of 8, 16, 32, and 64 μg/mL inhibited the development of the biofilm of P. aeruginosa PAO1, E. coli ATCC25922, and S. aureus MTCC3160 [ 51 ]. The results of the research presented by Maurer-Jones et al [ 52 ] showed that TiO2-NPs caused a slower growth of biofilm formed by Shewanella oneidensis .…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the development of biofilms by E. cloacae strain MC9, as mentioned, the absorbance-based crystal violet (CV) technique was used as previously described. ,, In brief, bacterial strains were exposed to 25–200 μg mL –1 concentrations of Cr, Cd, Pb, and Ni.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Today, it is known that increased antimicrobial resistance induced by the overuse of antibiotics represents a global public health challenge (Llor and Bjerrum, 2014). Issues associated with biofilm occurrence, as the predominant mode of microbial growth, and also one of the key survival strategies in which microbes can resist a number of chemical and physical stresses (Altaf et al, 2021), led to the growing demand for new antimicrobial agents, especially those of natural origin (Vaou et al, 2021). The main goal of this investigation was to evaluate the antimicrobial potential of ethanolic and methanolic extract made from sweet cherry stems, as well as to assess the impact of these extracts on the biofilm-forming capacity of different bacterial and fungal species.…”
Section: Introductionmentioning
confidence: 99%